Design and Implementation of a Computerized Balancing System - Ali, Jaafar Kh.; Najem, Saleh I. (Basrah Journal for Engineering Sciences, 2012)
In this work, a new computerized measurement system for multi-plane flexible rotor balancing has been designed and implemented. This system can be used to modernize and enhance conventional low-speed balancing machines or for field balancing applications. This system adds very important features to balancing machines such as multi-plane flexible rotor balancing, high accuracy, stability, and high dynamic range. Also, the proposed flexible rotor balancing technique permits accurate balancing of high-speed rotors utilizing low-speed balancing machines or field balancing at speeds lower than the critical speeds. The proposed digital Wattmetric technique in conjugation with advanced measurement circuitry have led to significant improvement in balancing accuracy even when the unbalance signal is buried into high level of noise.